Assessment of Hearing Profile and Psychosocial Reactions of Elderly with Tinnitus in Southwestern, Nigeria (Global Journal of Medical Research, 2021)
Tinnitus is an observed condition in which people experience different kinds of auditory sensation without any external stimulation. It is a kind of health-related condition with evidence of perception of noise or ringing in the ear/head without propagation of sound signals. Often, tinnitus occurs as a symptom of underlying conditions such as age-related hearing loss, drugrelated conditions, high blood pressure, ear injury, and evidence of accumulated earwax, cardiovascular disorders or metabolic disorder and/or a circulatory system disorder. Thus, without adequate health-care, individuals with tinnitus will experience communication difficulties and poor health-related quality of life. Evidently, research outcomes have established significant relationships among tinnitus, reduced auditory performance and hypertension, with little attention paid to psychosocial well-being of elderly with tinnitus. This study was therefore, designed to determine the types, degrees and patterns of hearing loss that existed among the elderly with tinnitus. The psychosocial reactions of the same elderly due to tinnitus - experience were also investigated. The study adopted an ex post facto research design.
Keywords: hearing status; quality of life; elderly; tinnitus